Collaborative Strategies in Authentic Assessment: Addressing Opportunities and Challenges in Post-Pandemic Indonesia - Mariati, Ni Komang Sri (Baileo: Jurnal Sosial Humaniora, 2025)
The transformation of learning in the post-pandemic era has heightened the demand for students’ skills in navigating real-world situations. This phenomenon necessitates both teachers and students to optimally prepare for the learning process, with authentic assessment serving as a strategic approach to address these challenges. This article aims to identify the challenges and benefits of implementing authentic assessment in the context of post-pandemic education in Indonesia and propose collaborative strategies as an innovative solution. The study employs a qualitative descriptive method based on a literature review, analyzing articles from reputable journals. Data were collected through selection, presentation, and conclusion-drawing processes. The findings reveal that authentic assessment offers significant benefits for both teachers and students, such as enhancing the relevance of learning to real-world needs and developing critical skills. However, several challenges persist, including the substantial time and cost requirements, pressure on teachers to design effective assessments, and student anxiety over unfamiliar assessment formats. To address these challenges, collaborative strategies between teachers and students are proposed as an innovative approach. These strategies involve intensive communication, joint planning, and continuous evaluation to optimize the implementation of authentic assessment. The novelty of this study lies in developing a collaborative approach to respond to the specific challenges of the post-pandemic era. Recommendations include integrating collaborative strategies into the education curriculum and providing teacher training to enhance the effectiveness of authentic assessments. These findings make a significant contribution to the development of social sciences and humanities, particularly in the context of educational reform in Indonesia.